Martian Atmospheric Temperature and Density Profiles During the First Year of NOMAD/TGO Solar Occultation Measurements. Issue 2 (22nd February 2023) - López‐Valverde, Miguel Angel; Funke, Bernd; Brines, Adrian; Stolzenbach, Aurèlien; Modak, Ashimananda; Hill, Brittany; González‐Galindo, Francisco; Thomas, Ian; Trompet, Loic; Aoki, Shohei; Villanueva, Gerónimo; Liuzzi, Giuliano; et al.
Abstract: We present vertical profiles of temperature and density from solar occultation (SO) observations by the "Nadir and Occultation for Mars Discovery" (NOMAD) spectrometer on board the Trace Gas Orbiter during its first operational year, which covered the second half of Mars Year 34. We used calibrated transmittance spectra in 380 scans, and apply an in‐house pre‐processing to clean data systematics. Temperature and CO2 profiles up to about 90 km, with consistent hydrostatic adjustment, are obtained, after adapting an Earth‐tested retrieval scheme to Mars conditions. Both pre‐processing and retrieval are discussed to illustrate their performance and robustness. Our results reveal the large impact of the MY34 Global Dust Storm (GDS), which warmed the atmosphere at all altitudes. The large GDS aerosols opacity limited the sounding of tropospheric layers. The retrieved temperatures agree well with global climate models (GCM) at tropospheric altitudes, but NOMAD mesospheric temperatures are wavier and globally colder by 10 K in the perihelion season, particularly during the GDS and its decay phase. We observe a warm layer around 80 km during the Southern Spring, especially in the Northern Hemisphere morning terminator, associated to large thermal tides, significantly stronger than in the GCM. Cold mesospheric pockets, close to CO2 condensation temperatures, are more frequently observed than in the GCM. NOMAD CO2 densities show oscillations upon a seasonal trend that track well the latitudinal variations expected. Results uncertainties and suggestions to improve future data re‐analysis are briefly discussed. Plain Language Summary: The detailed variation of temperature and density with altitude is of paramount importance to characterize the atmospheric state and to constrain the chemistry and dynamics as a whole. The Nadir and Occultation for Mars Discovery (NOMAD) instrument on board the Trace Gas Orbiter (TGO) has among its key targets the characterization of the thermal state with unprecedented vertical resolution. This is the target of this work, where we analyzed transmittance spectra obtained from the NOMAD solar occultation channel, with a state‐of‐the‐art retrieval scheme, adapted from Earth to Mars conditions and geometry. We applied it to the first year of TGO observations, which covered the last two Mars seasons of Mars Year 34. The results permit to study the temperature structure up to 90 km and its seasonal and latitudinal variations, revealing the impact of the MY34 Global Dust Storm, a warm layer at mesospheric altitudes not present in climate models, more frequent cold pockets than in current global climate models, and generally, colder temperature at those altitudes, all of which can be of importance for the validation of these climate models. Key Points: Temperature and density profiles up to 90 km are retrieved from Nadir and Occultation for Mars Discovery (NOMAD) first year of solar occultations, covering two seasons of Mars Year 34 NOMAD temperatures agree well with climate model predictions below 50 km but are wavier and globally colder by about 10 K at high altitudes We report large thermal tides producing warm layers at 80 km in the morning terminator. Also strong warming by the 2018 global dust storm